Cover Image. (9th December 2019) - Katayama, Sotaro; Doi, Masahiro; Ohtsuka, Toshiyuki
Abstract : The cover image is based on the Research Article A moving switching sequence approach for nonlinear model predictive control of switched systems with state‐dependent switches and state jumps by Sotaro Katayama et al., https://doi.org/10.1002/rnc.4804 .